(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
This systematic literature review addresses the pivotal role of in-service teacher training (INSET) in empowering educators to navigate the complexities of modern classrooms effectively. As educational landscapes continually evolve, teachers encounter diverse challenges necessitating ongoing professional development. The study aims to systematically analyse the existing literature to assess the efficacy of INSET programmes in equipping teachers with essential skills and strategies. By scrutinising a range of scholarly sources, including research articles and academic journals, the research synthesises insights into how INSET initiatives enhance teachers’ pedagogical practice and their ability to address contemporary educational challenges. Notably, it examines factors such as technological advancements and diverse learner populations, underscoring the imperative for teachers to adapt continually. Through this review, the study aims to offer a comprehensive understanding of both the strengths and limitations of current INSET practices. The findings hold potential implications for policymakers, educational institutions, and practitioners, informing the development of more tailored and effective INSET programmes. In conclusion, this systematic exploration seeks to elevate the quality of teacher training initiatives, thereby enriching students’ educational experience in today’s dynamic classrooms.